Antibacterial Activity of Ethanol Extract of Kemuning (Murraya Paniculata) Against Klebsiella pneumoniae ESBL by In Vitro Test - Wiyogo, Illona Okvita; Endraswari, Pepy Dwi; Setiawati, Yuani (Institute of Topical Disease Universitas Airlangga, 2021)
Klebsiella pneumoniae Extended-spectrum β-lactamase (ESBL) was one of the microorganism that cause nosocomial infection which resistant to beta-lactams antibiotics. Orange Jessamine (Murraya paniculata) was traditional medicine which believed has antibacterial components, such as: ï¬‚ avonoids, alkaloids, essential oils, coumarins, terpenoids, tannins, and saponins. In the previous studies, there was antibacterial activity in ethanolic extract of Murraya paniculata againsts E.coli, K.pneumoniae, S.typhi, E.faecalis, P.aeruginosa, S.ï¬‚ exneri, S.aureus, and S.sonneii with concentration 200 mg/ mL. There has not experiment about ethanolic extract of Murraya paniculata against Klebsiella pneumoniae ESBL yet. The aim of this study was to ï¬ nd out the in vitro antibacterial activity of ethanol extracts of Murraya Paniculata against Klebsiella pneumoniae ESBL Broth dilution method with concentration 200 mg/mL, 100 mg/mL, 50 mg/mL, 25 mg/mL, 12,5 mg/mL, 6,25 mg/mL, and 3,125 mg/mL were used for the determination of the Minimal Inhibitory Concentration (MIC). While the Minimal Bacterial Concentration (MBC) was assessed using streaking method in Nutrient Agar Plate. The highest concentration in this study was obtained from 100 g of Murraya paniculata leaves dissolved in 500 mL of 40% ethanol. The study was carried out 4 times replication. At the time of the sterility test extract, germ growth appeared on Nutrient Agar Plate media, so the extract was ï¬ ltered before being used for research. After incubation at 37 °C for 24 hours, growth of bacterial colonies on all agar plates was observed. The concentration of the ethanol extract of Murraya Paniculata (200 mg/mL) did not inhibit the growth of Klebsiella pneumoniae ESBL. The ethanol extracts of Murraya paniculata in concentration 200 mg/mL had no antibacterial activity against Klebsiella pneumoniae ESBL.